Improve Concept Understanding and Identifiability Using E-Modul Interactif Microalga - Shohifa Aulia Akbar; Diana Vivanti Sigit; Ratna Komala (Universitas Pendidikan Ganesha, 2024)
Students' difficulties understanding and identifying various forms of microalgae hurt their learning outcomes. As a result, students become increasingly bored with the learning process. This research aims to develop an interactive E-module to improve conceptual understanding and microalgae identification skills. This research uses research and development (R&D) procedures using the ADDIE development model. The subjects of this research were one media expert, material expert, design expert, biology lecturers for needs analysis, nine students for single trials, and eighteen students for small group trials. The methods used to collect data are observation and interviews. The data collection instrument uses a questionnaire. The data analysis technique uses qualitative, quantitative descriptive analysis and the N-gain test. The research results, namely that the interactive E-module obtained very feasible criteria based on the results of expert validation tests with a percentage greater than 80%. Based on the N-Gain test calculation results, the average concept understanding variable is 0.84, while the identification skills variable is 0.70, indicating a gain value greater than 0.7, which means it is very successful. It was concluded that the interactive E-module was practical and effective in improving student's understanding of concepts and identification skills.